Synthesis and Study of Chemical, Thermal, Mesomorphic, and Optical Properties of Terphenyls Modified with Nitrile Groups - M. L. Mota González; A. Carrillo Castillo; R. C. Ambrosio Lázaro; J. Flores Méndez; Mario Moreno; Priscy A. Luque; Dámaso Navarro (Journal of Chemistry)
We report the synthesis, characterization, and the thermotropic and photoluminescence properties of dialkoxyterphenyls with (T12-CN and T12-2CN) and without (T12) nitrile groups. These terphenyls were prepared through the Suzuki-Miyaura cross-coupling reaction using a palladium-based catalyst. The products obtained were analyzed as powders or after being drop-casted or spin-coated on glass. Nuclear Magnetic Resonance (1H NMR) and Fourier Transform Infrared (FTIR) spectroscopy techniques confirmed the structure and purity of the synthesized terphenyls. The mesomorphic behavior was studied by differential scanning calorimetry (DSC), polarizing optical microscopy (POM), and X-ray diffraction (XRD). T12 developed various mesophases, whereas T12-CN and T12-2CN displayed one single mesophase of low order over a wide temperature range. The films topology was studied by AFM and the optical properties were determined by ultraviolet-visible (UV-Vis) spectroscopy and spectrofluorometry. Higher roughness was found for the films prepared with the asymmetric terphenyl (T12-CN). The photoluminescence (PL) spectrum obtained for the asymmetric terphenyl (T12-CN) exhibited the expected characteristics with an emission band centered at 381 nm and an overtone around 760 nm.